Joint Attention During Live Person-to-Person Contact Activates rTPJ, Including a Sub-Component Associated With Spontaneous Eye-to-Eye Contact - Dravida, Swethasri; Noah, J. Adam; Zhang, Xian; Hirsch, Joy (Frontiers in Human Neuroscience, 2020)
Eye-to-eye contact is a spontaneous behavior between interacting partners that occurs naturally during social interactions. However, individuals differ with respect to eye gaze behaviors such as frequency of eye-to-eye contacts, and these variations may reflect underlying differences in social behavior in the population. While the use of eye signaling to indicate a shared object of attention in joint attention tasks has been well-studied, the effects of the natural variation in establishing eye contact during joint attention have not been isolated. Here we investigate this question using a novel two-person joint attention task. Participants were not instructed regarding the use of eye contacts; thus all mutual eye contact events between interacting partners that occurred during the joint attention task were spontaneous and varied with respect to frequency. We predicted that joint attention systems would be modulated by differences in the social behavior across participant pairs, which could be measured by the frequency of eye contact behavior. We used functional near-infrared spectroscopy (fNIRS) hyperscanning and eye-tracking to measure the neural signals associated with joint attention in interacting dyads and to record the number of eye contact events between them. Participants engaged in a social joint attention task in which real partners used eye gaze to direct each other’s attention to specific targets. Findings were compared to a non-social joint attention task in which an LED cue directed both partners’ attention to the same target. The social joint attention condition showed greater activity in right temporoparietal junction than the non-social condition, replicating prior joint attention results. Eye-contact frequency modulated the joint attention activity, revealing bilateral activity in social and high level visual areas associated with partners who made more eye contact. Additionally, when the number of mutual eye contact events was used to classify each pair as either “high eye contact” or “low eye contact” dyads, cross-brain coherence analysis revealed greater coherence between high eye contact dyads than low eye contact dyads in these same areas. Together, findings suggest that variation in social behavior as measured by eye contact modulates activity in a subunit of the network associated with joint attention.